Computational approach to solving a layered behaviour differential equation with large delay using quadrature scheme - Pandi, Amala; Mudavath, Lalu; Kolloju, Phaneendra (Zielona Góra: Uniwersytet Zielonogórski)
This paper deals with the computational approach to solving the singularly perturbed differential equation with a large delay in the differentiated term using the two-point Gaussian quadrature. If the delay is bigger than the perturbed parameter, the layer behaviour of the solution is destroyed, and the solution becomes oscillatory.
Keywords: singularly perturbed delay differential equation; layer behavior; fitting parameter; Gaussian quadrature